A new critically endangered slippery frog (Amphibia, Conrauidae, Conraua) from the Atewa Range, central Ghana - Neira-Salamea, Karla; Ofori-Boateng, Caleb; Kouamé, N’goran G.; Blackburn, David C.; Segniagbeto, Gabriel H.; Hillers, Annika; Barej, Michael F.; Leaché, Adam D.; Rödel, Mark-Oliver (Zootaxa, 2021)
Forty-nine years after the last description of a slippery frog, we describe a seventh species of the genus Conraua. The new Conraua is endemic to the Atewa Range Forest Reserve, central Ghana, and is described based on genetic, bioacoustics, and morphological evidence. Recent molecular phylogenetic and species delimitation analyses support this population as distinct from nominotypical C. derooi in eastern Ghana and adjacent Togo. The new species is sister to C. derooi, from which it differs 4% in the DNA sequence for mitochondrial ribosomal 16S. Genetic divergences in 16S to other species of Conraua range from 4–12%. The new species is distinguished morphologically from its congeners, including C. derooi, by the combination of the following characters: medium body size, robust limbs, lateral dermal fringing along edges of fingers, cream ventral color with brown mottling, the presence of a lateral line system, indistinct tympanum, the presence of inner, outer, and middle palmar tubercles, and two subarticular tubercles on fingers III and IV. We compare the advertisement calls of the new species with the calls from C. derooi and find that they differ by duration, frequency modulation, and dominant frequency. We discuss two potential drivers of speciation between C. derooi and the new species, including river barriers and fragmentation of previously more widespread forests in West Africa. Finally, we highlight the importance of the Atewa Range Forest Reserve as a critical conservation area within the Upper Guinean biodiversity hotspot.